2014
DOI: 10.1177/0890334414553247
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Characteristics Associated with Milk Leptin Content in a Sample of Filipino Women and Associations with Infant Weight for Age

Abstract: The association between maternal body composition, milk leptin, and infant growth persists in mothers with lean body composition. Milk leptin is not associated with growth in older infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 49 publications
7
30
0
1
Order By: Relevance
“…Moreover, the majority of previous studies analysed leptin in skim HM in cross-sectional cohorts and are restricted to the first and third months postpartum [25], limiting their ability to determine leptin profiles during lactation in women of varying BC. Only three studies have analysed %FM using dual-energy X-ray absorptiometry (DXA) [24], skinfold measures [63] and bioelectrical impedance analysis [65] and they found a strong association between %FM and skim milk leptin, consistent with the results from our study. Interestingly, Khodabakhshi et al (2015) [65] found association between HM leptin and both %FM and BMI only in the subset of mothers of obese infants but not in the subset of mothers of normal infants, although these two groups did not differ by BMI or leptin concentration.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the majority of previous studies analysed leptin in skim HM in cross-sectional cohorts and are restricted to the first and third months postpartum [25], limiting their ability to determine leptin profiles during lactation in women of varying BC. Only three studies have analysed %FM using dual-energy X-ray absorptiometry (DXA) [24], skinfold measures [63] and bioelectrical impedance analysis [65] and they found a strong association between %FM and skim milk leptin, consistent with the results from our study. Interestingly, Khodabakhshi et al (2015) [65] found association between HM leptin and both %FM and BMI only in the subset of mothers of obese infants but not in the subset of mothers of normal infants, although these two groups did not differ by BMI or leptin concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Increased serum amino acid concentrations are present in mothers with more adipose tissue [39], leading to more amino acids transferred to the breast and HM [70], explaining the positive relationship between maternal adiposity and HM protein concentrations [42]. This study has found that higher %FM but not BMI was associated with higher protein concentrations, which is similar to Quinn et al [63] who reported %FM to be more precise measure of adiposity reporting stronger correlation with HM leptin, thus the more precise measure of maternal BC is desirable in mechanistic research.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The few earlier studies investigating relationships between protein content in human milk and maternal nutritional status are contradictory. Some reporting a positive correlation between protein and maternal adiposity assessed by BMI [2,7,12,21], whereas Quinn et al [23] and Kugananthan et al [17] have found that higher percentage of fat mass but not BMI was associated with higher protein concentrations. By contrast, Bachour et al [2] reported negative association between protein content and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence shows that breast milk is highly complex with significant variation between women in concentrations of bioactive compounds beyond that of basic macro nutriture. [2][3][4][5][6] Little is known about the association between maternal obesity and non-nutritive components of breast milk. Given that nearly 60% of women enter pregnancy with overweight or obesity in the U.S., 7 and approximately 50% exceed the Institute of Medicine (IOM) gestational weight gain (GWG) recommendations, 8 it is important to examine the effect of maternal weight status on breast milk composition, and in turn, whether this affects the offspring's risk of future obesity and other adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%